Leadership in Technical Fields Through a Gender Lens - Irina S. Oblova (Changing Societies & Personalities)
Although women have fought for labor rights for many years, they continue to be underrepresented at almost all levels of decision-making. The present study aims to provide insights into female leadership in technical fields both in the EU and in Russia. The article examines the principal leadership aspects of women’s status and career experiences. To identify the ingredients of successful leadership, the Multifactor Leadership Questionnaire and interviews were administrated to a sample of 200 mining students and 40 senior executives. The research data were processed by means of correlative, regressive, and autocorrelation analyses. To track the consistency of the identified leadership factors, female heads of enterprise divisions and university departments shared their views on career progress. The Mann–Whitney U test was employed to analyze the leadership factors. Studies indicate that the more senior the position is, the fewer women there are in leadership roles. Women’s progress in technical careers is hindered both by their own uncertainty and judgments made by others about their abilities. To rectify this situation, practices for encouraging young women to pursue technical careers are recommended along with approaches for maintaining them within the career structure. The research findings also indicate a positive emerging global trend towards increased gender diversity in technical fields.